PENGARUH INVOLVEMENT, CUSTOMER PARTICIPATION, COMMITMENT TERHADAP LOYALTY YANG DIMEDIASI OLEH CUSTOMER ENGAGEMENT PADA MEDIA SOSIAL "FACEBOOK" - Tiara Paramita; Sri Vandayuli Riorini (Bussman Journal : Indonesian Journal of Business and Management, 2023)
This study aims to investigate the influence of important factors in customer interaction on Facebook social media on customer loyalty through the process of customer engagement and engagement. The concept of customer engagement refers to the level of depth and intensity of customer interaction with a brand through social media platforms. The factors studied include the level of customer engagement, customer participation, and customer commitment. This study used regression analysis methods to examine the relationship between these variables and how they affect each other. Data was taken through an online survey filled out by respondents who are active users of Facebook social media who have interactions with certain brands or companies on the platform. The results of this study are expected to provide deeper insights into how customer interactions on Facebook social media can affect customer loyalty through customer engagement mechanisms. The practical implications of this research could help companies to devise more effective strategies in building and maintaining strong relationships with customers through social media, thereby increasing customer loyalty and their engagement with brands